ATM locator mobile application - Yen Leng, Lim (2012)
Global Positioning System (GPS) is has been widely used in many fields.At first,it is used for the purpose of military forces needs.Then,the uses of GPS has extended into people’s lifestyle,where they can use it for hiking purpose, as traveling direction, and etc.Besides that,it is useful for user to search for nearby amenities – restaurants,petrol stations,banks and more,especially for someone who is unfamiliar to new location.Therefore, the aim of this paper is to propose an ATM locator for mobile application. Developed methods are entirely mobile web-based.This system will instantly tells the user where does the closest ATM located from their current location.Hence,this system is developed slight similar to the existing system like Maybank ATM locator,where this proposed system can locate all kind of Bank company’s ATM instead of only the Maybank ATM. Besides that, it is a hybrid mobile application. Hybrid app is a native, downloadable app and it uses both browser interfaces and native mobile components.With HTML5 and JavaScripts, the browsers are becoming capable of accessing a phone’s built-in features like contacts,camera etc. In order to keep the timeline for this system to be finish at the appointed time.So,a System Development Life Cycle (SDLC) was referred.